Assessment of Knowledge on the Mode of Transmissions and Preventions of Hepatitis-B Among Undergraduate Students in Nigeria - Afolabi Fasoranti Joseph (Journal of Social Behavior and Community Health, 2021)
Background: Hepatitis B, which is caused by the Hepatitis B virus (HBV), is a global health problem that has resulted in high morbidity and mortality with knowledge and awareness about the occurrence and mode of transmissions relatively low among the populace. Therefore, this study examined knowledge on the mode of transmission and preventions of hepatitis B among undergraduate students in Lagos, Nigeria. Methods: The cross-sectional descriptive research was used, and a multi-stage sampling technique was adopted to select three hundred respondents which comprised male and female from three tertiary institutions in Lagos state in 2019. Hepatitis B Knowledge Questionnaire with a reliability index of 0.74 was used for data collection. The descriptive statistics of frequency count and percentages was used to analyse the demographic characteristics of respondents while the chi-square test was used to determine associations between categorical variables. Results: The results revealed that a high proportion of the respondents had poor knowledge about the transmission and prevention of hepatitis B. The result revealed that the p-value ≤ 0.05 was considered statistically insignificant. Therefore, the study revealed that there is no significant relationship between gender and hepatitis B. Conclusion: A critical level of public awareness and vaccination coverage, particularly among students, is essential to decrease Lagos' burden.